Diversity and Community Structure of Plant Parasitic Nematodes in Khasi Mandarin Orchards of Assam, India - Kumar, K. Kiran; Das, Ashis K. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during December, 2017–February, 2018 in the soil rhizosphere of Khasi mandarin orchards across four districts (Kamrup (R), Kamrup (M), Tinsukia and Biswanath) in Assam, India to study the diversity and community structure of plant parasitic nematodes (PPN). Soil samples collected from different orchards revealed the presence of six major PPN genera viz., Tylenchulus semipenetrans, Helicotylenchus sp., Tylenchorhynchus sp., Hoplolaimus sp., Pratylenchus sp. and Rotylenchulus sp. Among the identified PPN, T. semipenetrans was the most abundant species observed in all surveyed districts, indicating its widespread distribution and potential as a key threat to Khasi mandarin production. It was followed by Helicotylenchus sp. and Tylenchorhynchus sp. in terms of abundance. The highest juvenile count of T. semipenetrans was recorded in Tinsukia, while the lowest was observed in Kamrup (M). The remaining PPN genera showed variable occurrence depending on the location and orchard condition. The nematode community structure was thoroughly analyzed using various ecological parameters, including frequency, density and prominence value. T. semipenetrans had the highest frequency (AF=100%), relative frequency (RF=38.12%), and prominence value (PV=422.25), establishing it as the dominant PPN in Khasi mandarin orchards. This detailed identification and community analysis of PPN genera associated with Khasi mandarin orchards provided fundamental information for designing suitable nematode management strategies to minimize yield losses, thereby enhancing the sustainability and productivity of Khasi mandarin cultivation and contributing to long-term food security in the region.